The tangible video editor: Collaborative video editing with active tokens. - Zigelbaum, Jamie.; Horn, Michael S.; Shaer, Orit.; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
In this paper we introduce the Tangible Video Editor (TVE), a multi-user, tangible interface for sequencing digital video. We present a new approach to tabletop interaction by using multiple handheld computers embedded in plastic tokens. Drawing from the rich physical experience of tradition film editing techniques we designed the TVE to engage multiple users in a collaborative process and encourage the exploration of narrative ideas. We used active tokens to provide a malleable interface, enabling users to organize the interface components in unspecified ways. Our implementation improves upon common projection-based tabletop interfaces in a number of ways including a design for use beyond dedicated two dimensional spaces and a naturally scaling screen resolution.